A study on the etiological agent and clinico-mycological correlation of fingernail onychomycosis in eastern India - Das Nilay; Ghosh Pramit; Das Suchibrata; Bhattacharya Susmita; Dutta Rathindra; Sengupta Sujit (Wolters Kluwer Medknow Publications, 2008)
Background: Onychomycosis manifests itself in various forms, notably onychodystrophy, onycholysis, subungual hyperkeratosis, or nail-plate discoloration. Not necessarily nail changes mentioned here should always be of fungal origin. Objective: The present study is planned to get an idea about etiological agent and clinical correlation in fingernail onychomycosis. Materials and Methods: Nail-clipping and subungual debris of patients with above mentioned nail changes were subjected to KOH preparation. Culture was done on SDA and SDCCA media. Species identification was done by colony character, pigment production, LCB staining, and some special tests like germ tube test, etc. Results: Out of 85 cases, 44 cases showed the growth of fungus, amounting to 51.76% positivity. Among those 44 cases, the infective fungal agents were predominantly dermatophytes (50%), and the rest were due to yeasts (27.27%) and moulds (22.72%). Among the different species, Trichophyton rubrum (29.54%) accounted for the majority of dermatophytes; Candida albicans (11.78%) was the predominant yeast; and Aspergillus niger (18.18%) the commonest mold. No significant association could be established between the different fungal species and various clinical manifestations. Positive results were found more with fungal culture (95.45%) than KOH preparation (63.64%). Conclusion: The results show that nail changes are not always a reliable marker for predicting the causative organism, and relying only on the clinical manifestation (i.e., pattern of nail changes) in the diagnosis of onychomycosis is often misleading. The present study highlights the need for microbiological confirmation in case of onychomycosis.